POSITIONING PROCESS MODELING OF AUTOMATED MANUFACTURING EQUIPMENT ROTARY-DIVIDED MECHANISMS WITH HYDRAULIC LINES - A.M. AL-QUDAH; V.S., SIDORENKO; V.I. GRISHENKO (Advanced Engineering Research)
Increasing the accuracy and high acting of positioning for technological machines and their mechanisms is of great importance. It is achieved by inventing and modification of hydro-mechanical devises with hydraulic connecting lines. In this statement the positioning process of such devises is modeling, relationships between velocity of hydraulic motor(executive mechanism), backpressure of brake valve and precise stopping is gained.